Kerentanan Sosioekonomi Rumah Tangga Petani Akibat Konversi Lahan (Studi Kasus Kabupaten Bogor Jawa Barat) - Nudya Wiyata; Arya Hadi Dharmawan; Eka Intan Kumala Putri (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Land conversion is one of the consequences of population growth. Bogor as a buffer zone of the capital city and Bekasi, Depok, Tangerang has significant increase number of developed land. The urban sprawl drove land use change from farmland, paddy fields, and forest area. This study tries to identify livelihood assets and livelihood structures and to analyse the socioeconomic vulnerability index of farm households as a result of land conversion in Cibungbulang Sub-district, Bogor Regency. The research focused on two villages, Cemplang and Situ Udik. We surveyed 35 households from each village to collect data on various vulnerability domains and 27 socioeconomic indicators. We built and weighted these indicators base on local stakeholders, farmers, prior researches and literature studies. The research results showed that both villages are moderate in vulnerability and are still able to deal with the existing shocks. SeVI of Cemplang is 0.51 and Situ Udik’s 0.37. There are five livelihood assets used by respondents to survive; human capital, economic, social, physical and financial.